Analysis of Challenges Facing Rice Processing in Nigeria. (26th October 2015) - Ajala, A. S.; Gana, A.
Abstract : Rice is the most economically important food crop in many developing countries and has also become a major crop in many developed countries where its consumption has increased considerably. It has become necessary to meet the demand of the world's current population growth rate, and the least costly means for achieving this aim is to increase rice productivity, wherever possible. The main challenges encountered by rice processors in Nigeria are to find appropriate solutions for quality rice processing. Therefore this work provides basic information about the challenges of rice processing and focuses on the challenges faced by the small scale rice processors and reasons for continuous rice importation with a view to guiding decision-making to be self-sufficient in rice production, thereby making some improvement in Nigerian economy.